Effect of isoproteinous feed on growth and survival of tilapia (Oreochromis niloticus) fry (Journal of the Bangladesh Agricultural University, 2012)
A four week experiment was conducted to evaluate the effect of isoproteinous (35%) feed prepared named diet 1, 2, 3 and 4 respectively by substituting 0%, 50% , 75% and 100% fish meal with meat and bone meal in view of preparing a cost effective tilapia (Oreochromis niloticus) fry feed. The four experimental diets (diet 1 to 4) each were randomly assigned to twelve hapas with three replications. Tilapia fry (0.011g) were randomly stocked in 100 fry/9ft² hapa and fed five times a day up to their apparent satiation. The results of the study showed that the weight gain, specific growth rate (SGR), the apparent net protein utilization value and survival (%) of the fish were significantly  (P